Characterization of the Beekeeping Value Chain: Challenges, Perceptions, Limitations, and Opportunities for Beekeepers in Kayonza District, Rwanda - Borden Mushonga; Landouard Hategekimana; Gervais Habarugira; Erick Kandiwa; Alaster Samkange; Basiamisi Victor Ernest Segwagwe (Advances in Agriculture)
A survey was undertaken to characterize the honey production value chain and identify the challenges, limitations, and opportunities for beekeepers in Kayonza District, Eastern Rwanda, in light of the stagnation of the apiculture industry. The majority (86%, n = 100) of the beekeepers were adult males. Most of the respondents (71%) lacked primary level education. The majority of the hives were made from hollow tree logs (40%), tree barks (12%), banana leaves/bark (11%), cow dung (8%), mud (7%), grass (6%), tree leaves (6%), and the rest (20%) were improved beehives, particularly Langstroth hives. The hive pests encountered were hive beetles (25%), small black ants (19%), wax moths (12%), lizards (8%), termites (7%), birds (6%), mites (3%), and mice (2%). Fifty-five percent of the respondents hung their hives on trees to prevent pest invasion with 95% effectiveness, 25% frequently smoked their hives with 85% effectiveness, 16% cleared the bushes around apiaries with 55% effectiveness, and 4% used traditional plant insect repellents with 35% effectiveness. Forty-one percent of the respondents lacked adequate information on beekeeping, 25% had inadequate time to work on apiaries, 24% had inadequate technical knowledge and implements, and 10% needed additional labour for managing apiaries. Based on the results of this study, beekeeping in Kayonza is still largely traditional, characterized by the use of antiquated production methods and underutilization of available marketing channels. Perceptions in the district are that beekeeping is for the poor and illiterate. Challenges and limitations of beekeeping in Kayonza District include lack of education, gender bias, pests and diseases, absconding and swarming of bees, high costs, and lack of modern apicultural equipment. However, the potential for developing beekeeping enterprise (opportunities) is immense given the abundance of wild bee populations, possibility of women participation, abundance of honey collection centres (market), and availability of technical support from Government and development agencies. In conclusion, this study advocates the need for intervention measures to educate and promote production and marketing of quality honey, tackle pest and disease for beekeepers and boost Rwanda’s apiculture industry.